2008
DOI: 10.1117/1.2940366
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization between aequorea fluorescent proteins does not affect interaction between tagged estrogen receptors in living cells

Abstract: Forster resonance energy transfer (FRET) detection of protein interaction in living cells is commonly measured following the expression of interacting proteins genetically fused to the cyan (CFP) and yellow (YFP) derivatives of the Aequorea victoria fluorescent protein (FP). These FPs can dimerize at mM concentrations, which may introduce artifacts into the measurement of interaction between proteins that are fused with the FPs. Here, FRET analysis of the interaction between estrogen receptors (alpha isoform, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Images were collected between 30 and 40 min post-treatment on a previously described microscope using a 20ϫ/0.75 NA objective (22,23). Initial studies conducted on cells treated with estradiol for 2 hours showed similar results.…”
Section: Methodsmentioning
confidence: 55%
See 4 more Smart Citations
“…Images were collected between 30 and 40 min post-treatment on a previously described microscope using a 20ϫ/0.75 NA objective (22,23). Initial studies conducted on cells treated with estradiol for 2 hours showed similar results.…”
Section: Methodsmentioning
confidence: 55%
“…The binding at 30 min, therefore, had reached steady state, which is a prerequisite for equilibrium biochemical analysis. The Acceptor, Donor and FRET images were collected in rapid succession, with the Acceptor images collected at two integration times to capture large variations in YFP-SRC expression levels, as previously described (22,23). Image collection was followed by previously described semi-automated procedures for background-subtraction, nuclei identification, and debris identification/elimination (22).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations